Communicative Resilience Under Conditions of Backlash and Information Disorder - Calvo, Dafne; Iranzo Cabrera, Maria (PARTECIPAZIONE E CONFLITTO, 2026)
This introductory essay presents the special issue Communicative Resilience: Civil Society’s Response to Information Disorders and argues for a shift in how resilience is understood in communication research. Rather than treating resilience as recovery or as a set of technical fixes (fact-checking, media literacy, or platform moderation), the essay frames it as a transformative, everyday process of meaning-making. In contexts marked by polarization, backlash, and attention-driven platforms, civil society actors sustain action by recombining identities, narratives, emotions, and viewpoints, while building networks of coordination and mutual support. Across the cases gathered in the issue, resilience emerges as multi-actor and relational. It relies on alliances that extend beyond institutions, develops alternative infrastructures for visibility and trust, and contests dominant frames that normalize hate or disinformation. The contributions collectively show how these communicative practices can widen participation and help publics bounce forward under pressure.